Locating the electrical junctions in Cu(In, Ga)Se2 and Cu2ZnSnSe4 solar cells by scanning capacitance spectroscopy. (9th August 2016) - Xiao, Chuanxiao; Jiang, Chun‐Sheng; Moutinho, Helio; Levi, Dean; Yan, Yanfa; Gorman, Brian; Al‐Jassim, Mowafak
Abstract: We determined the electrical junction (EJ) locations in Cu(In, Ga)Se2 (CIGS) and Cu2 ZnSnSe4 (CZTS) solar cells with ~20‐nm accuracy by developing scanning capacitance spectroscopy (SCS) applicable to the thin‐film devices. Cross‐sectional sample preparation for the SCS measurement was developed by high‐energy ion milling at room temperature for polishing the cross section to make it flat, followed by low‐energy ion milling at liquid nitrogen temperature for removing the damaged layer and subsequent annealing for growing a native oxide layer. The SCS shows distinct p‐type, transitional, and n‐type spectra across the devices, and the spectral features change rapidly with location in the depletion region, which results in determining the EJ with ~20‐nm resolution. We found an n‐type CIGS in the region next to the CIGS/CdS interface; thus, the cell is a homojunction. The EJ is ~40 nm from the interface on the CIGS side. In contrast, such an n‐type CZTS was not found in the CZTS/CdS cells. The EJ is ~20 nm from the CZTS/CdS interface, which is consistent with asymmetrical carrier concentrations of the p‐CZTS and n‐CdS in a heterojunction cell. Our results of unambiguously determination of the junction locations contribute significantly to understanding the large open‐circuit voltage difference between CIGS and CZTS. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We determined the electrical junction (EJ) locations in Cu(In, Ga)Se2 (CIGS) and Cu2 ZnSnSe4 (CZTS) solar cells with ~20‐nm accuracy by developing scanning capacitance spectroscopy applicable to the thin‐film devices. We found an n‐type CIGS in the region next to the CIGS/CdS interface, and the EJ is at ~40 nm from the interface at the CIGS side, thus a homojunction of the cell. In contrast, such an n‐type CZTS was not found in the CZTS/CdS cells and the EJ is ~20 nm from the CZTS/CdS interface, which is consistent with asymmetrical carrier concentrations of the p‐CZTS and n‐CdS in a heterojunction cell.